The promise and perils of urban land restitution in Latvia - Rowen, Jamie (International journal of transitional justice, 2021)
In this article we address the transitional justice policy of restitution in kind with a case study of urban land reform in Latvia. Contributing to scholarship on the challenge of property reforms after generations of dispossession, we examine the economic, social and political meanings of property restitution in this post-Soviet context. Using process-tracing techniques to examine the creation and implementation of Latvia’s policy in the aftermath of independence from the Soviet Union, we illustrate specific challenges of restitution in kind where property changed through the construction of new buildings occupied by tenants. Financial disputes between landowners and tenants map on to ethnic and political divisions in Latvia, and a policy once seen as a remedy is now in need of a remedy.